Public Health Bachelor’s Perception of Skills Needed to Work in the Health Office: A Qualitative Study among Alumni from Universitas Negeri Malang - Mawarni, Dian; Hapsari, Anindya; Tama, Tika Dwi; Rachmawati, Windi Chusniah; Masyiyah, Shofiyatul; Firdausi, Nurul Jannatul (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Health is a dynamic, emerging, and interdisciplinary field. To address current health problem challenges, we need a public health workforce constantly adaptable and equipped with the newest skills. This study was to explore the skills needed by public health bachelor’s to work in the health office. Methods: We used qualitative methods. A total of six participants took part in this study. Interviews were held virtually via Zoom Platform in September 2022 using a semi-structured interview guide. Interviews were audio-visual recorded, and transcribed verbatim. The transcripts were coded by members of the research team and a thematic analysis was conducted. Results: The majority of participants get jobs in the office through different work entrances. Our study identifies that participants need technical and interpersonal skills to support their job in the health office. Outside learning contributes to developing skills needed by participants. Conclusion: This study represents an initial endeavor to identify the core work-related skills for public health graduates who work in the health office. Future research is needed for longitudinal larger scale quantitative studies to confirm our qualitative findings. In addition, our findings promote transformations on learning for Bachelor of Public Health Program more comprehensively.